Review of Islamic Criminal Law on The Criteria of Justice Collaborators In Relation to The Law on Protection of Witnesses and Victims - Lestari, Napuli Ayu; Najmudin, Deden; Azazi, Yusuf (Journal Analytica Islamica, 2025)
Organized crime poses a major challenge in modern law enforcement due to its covert nature. One approach used to uncover such crimes is through the role of a justice collaborator, namely a perpetrator who is willing to cooperate with law enforcement authorities. This study aims to analyze the criteria for a justice collaborator according to the Witness and Victim Protection Act and to examine its relevance from the perspective of Islamic criminal law. The method used is normative juridical with statutory, conceptual, and comparative approaches. The results of the study indicate that there are fundamental differences between positive law and Islamic criminal law in assessing the eligibility of a witness, particularly concerning the requirement of justice. Nevertheless, from the perspective of maqasid al-sharia and the urgency of uncovering major crimes, the role of a justice collaborator can be considered relevant and not in contradiction with the principles of Islamic law. The novelty of this study lies in the integrative approach that examines the synchronization between positive legal norms and Islamic justice values in protecting cooperative perpetrators. This study enriches the discourse on criminal law by offering a dualistic perspective that is rarely raised in previous studies. However, this study is limited to a normative study of regulations and doctrines, without examining the empirical implementation or response of judicial institutions in practice. The results are expected to be a conceptual basis for the development of more inclusive and equitable legal policies.